KAJlAN BIOLOGI IKAN PARI BATIMMONDOL (Himantura gerrardi) FAMILI DASYATIDAE YANG DIDARATKAN DI PPN PENJAJAB, KECAMATAN PE,NIANGKAT, KABUPATEN SAMBAS, KALIMANTAN BA RAT - Sudarso, Jumadi (Jurnal Perikanan dan Kelautan, 2007)
The aim of this study is to observe the biological aspects such as length, weight,length weight correlation and sex ratio. The study was done in October 2006.There were 199 females rays and 166 males rays on the observation, thus theywere measured as length and weight. Therefore, it intended to achieve the weightlength connection of those rays. The result of the observation was that the value ofmales b and females was not differ obviously by 3 or b = 3. It showed that thegrowth figure of male and female's Himantura gerrardi was isometric, whichmeans that the growing of the length was balanced from the growing of theweight. The sex ratio between males and females is 1:1.2. After testing of Test X2,it had been found that there were not significant differences between male andfemale. It also emphasized that the capture had been done for the observation wason the breeding season, thus the males and females were altogether.